2016
DOI: 10.1007/s40808-016-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous modelling and forecasting of hourly dissolved oxygen concentration (DO) using radial basis function neural network (RBFNN) based approach: a case study from the Klamath River, Oregon, USA

Abstract: In the present study, we developed and compared two artificial intelligences technique (AI) for simultaneous modelling and forecasting hourly dissolved oxygen (DO) in river ecosystem. The two techniques are: radial basis function neural network (RBFNN) and multilayer perceptron neural network (MLPNN). For the purpose of the study, we choose two stations from the United States Geological Survey: (USGS ID: 421015121471800) at Lost River Diversion Channel nr Klamath River, Oregon, USA (Latitude 42°10 0 15 00 , Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…The study results show a consistency with other studies. For example, Heddam [54] in a separate study demonstrated that water temperature and pH can predict DO levels with an enough level of confidence. The results and insight from this study can also offer practical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The study results show a consistency with other studies. For example, Heddam [54] in a separate study demonstrated that water temperature and pH can predict DO levels with an enough level of confidence. The results and insight from this study can also offer practical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The neurons are organized in layers and interconnected with weighted connections corresponding to human brain synapses. Multilayer perceptron neural network (MLPNN) is the most common type of ANN, and it has been applied for many applications include river flow forecasting, pigment concentration in a river, and water quality prediction [26]- [28]. Its architecture can be described, as shown in Fig.…”
Section: Basics Of Artificial Neural Networkmentioning
confidence: 99%
“…Assuming the number of input parameters is denoted by k, and the number of neurons in the hidden layer is given as m. Mathematically, the input to the output structure of the MLPNN can be formulated as follows [26]:…”
Section: Basics Of Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Para comparar os resultados do modelo desenvolvido foram utilizados os modelos de regressão linear e perceptron multi-camada e concluiu que o modelo proposto apresenta melhor resultado de previsão quando o parâmetro apresenta alta variabilidade no conjunto de dados. [Heddam 2016] comparou a capacidade dos modelos Radial Basis Function Neural Network (RBFNN) e Multilayer Rede Neural Perceptron (MLPNN) para modelagem simultânea e previsão de concentração de OD, utilizando variáveis (pH, TE, SC e SD) da qualidade daágua e valores antecedentes de DO. Conseguiu prever com até 72 horas a frente a concentração de OD, mas ressaltou que para um atingir um melhor desempenhó e necessária uma base de dados com mais de 1 ano de dados.…”
Section: Trabalhos Relacionadosunclassified